Association of downregulated HDAC 2 with the impaired mitochondrial function and cytokine secretion in the monocytes/macrophages from gestational diabetes mellitus patients. (7th April 2016) - Qu, Xin; Yu, Hongna; Jia, Bei; Yu, Xiaoyan; Cui, Qing; Liu, Zhifen; Sun, Chengming; Chu, Yongli
Abstract: Gestational diabetes mellitus (GDM) is associated with an increased risk of type 2 diabetes (T2DM) and cardiovascular diseases in later life, yet with underlying mechanisms unclear. The present study was to explore the association of upregulated histone deacetylase 2 (HDAC 2) with the impaired mitochondrial function and the cytokine secretion in the monocytes/macrophages from GDM patients. In this study, we examined the mitochondrial function, proinflamatory cytokine secretion and the HDAC 2 level in the serum or in the monocytes/macrophages from GDM patients, investigated the influence by HDAC 2 inhibitor, AR‐42 (N‐hydroxy‐4‐[[(2S)‐3‐methyl‐2‐phenylbutanoyl]amino]benzamide), on the mitochondrial function and cytokine secretion in the isolated GDM monocytes/macrophages. Results demonstrated an increased mitochondria size, mitochondrial superoxide and reactive oxygen species (ROS) production, and an undermined mitochondria membrane potential (MMP) in the GDM monocytes/macrophages. And the serum levels of interleukin (IL)‐1β, tumor necrosis factor (TNF)‐α and IL‐6 were also markedly higher in the GDM pregnancies, while the expression and activity of HDAC 2 was downregulated. Moreover, AR‐42‐mediated HDAC 2 inhibition in vitro contributed to the impaired mitochondrial function and the proinflamatory cytokine secretion. In conclusion, this study suggests an association of the impaired mitochondrial function and the promoted proinflamatory cytokine secretion with the reduced HDAC 2 activity in GDM. These findings may present HDAC 2 as a target for GDM treatment.